LATAR BELAKANG PENDIDIKAN ORANG TUA TERHADAP PERKEMBANGAN SOSIAL ANAK USIA 5-6 TAHUN - Nurlita, Tesi Ayi; Sumardi, Sumardi; Mulyadi, Sima (JURNAL PAUD AGAPEDIA, 2020)
This research is related to the educational background of parents towards the social development of children aged 5-6 years in the village of Cipertani. The research method used is descriptive qualitative with data collection techniques in the form of questionnaires to research respondents. Respondents in this study were 30 parents who have children aged 5-6 years living in the village Cipertani Rt.05 Rw.08. The educational background of parents in the Cipertani village of 30 respondents ranged from 26.7% of elementary school graduates, 6% of junior high schools, 33.3% of high schools and 20% of universities. Children's social development includes the child's response to playing with peers, the child's cooperative nature, and the attitude of responsibility of the child. The child's social development questionnaire filled with parents includes both positive and negative statements with five alternative answers on a scale of 1-5. Children's social development is divided into four categories 20% categorized as undeveloped, 20% -35% still developing, 36% -65% developing as expected, and 66-100% developing very well. The social development of children in Cipertani village has an average of 47.18% categorized as developing according to expectations. The results of the regression test showed that the value of P (P-Value) = 0.315 stated that Ho was rejected, so it can be concluded that the educational background of parents did not affect the social development of children aged 5-6 years in Cipertani village. Penelitian ini berkaitan dengan latar belakang pendidikan orang tua terhadap perkembangan sosial anak usia 5-6 tahun di kampong Cipertani. Metode penelitian yang dipakai adalah kuntitatif deskriptif dengan teknik pengumpulan data berupa penyebaran angket pada responden penelitian. Responden dalam penelitian ini adalah 30 orang tua yang memiliki anak usia 5-6 tahun tinggal di kampung Cipertani Rt.05 Rw.08. Latar     belakang pendidikan orang tua di kampung cipertani dari 30 responden berkisar dari tamatan SD sederajat sebanyak 26,7%, SMP sederajat sebanyak 6%, SMA sederajat sebanyak 33,3%, dan Perguruan Tinggi sebanyak 20%. Perkembangan sosial anak mencakup respon anak bermain dengan teman sebayanya, sifat kooperatif anak, dan sikap tanggung jawab anak. Angket perkembangan social anak yang diisi orang tua mencakup pernyataan baik itu positif dan negatif dengan lima alternatif jawaban dengan skala nilai 1-5. Perkembangan social anak dibagi menjadi empat kategori 20% dikategorikan belum berkembang, 20%-35% masih berkembang, 36%-65% berkembang sesuai harapan, dan 66-100% berkembang sangat baik. Perkembangan sosial anak di kampung Cipertani mempunyai rata-rata 47,18% dikategorikan ke dalam berkembang sesuai harapan. Hasil penelitian uji regresi menunjukan nilai P(P-Value) = 0,315 dinyatakan bahwa Ho ditolak maka dapat disimpulkan bahwa latar belakang pendidikan orang tua tidak berpengaruh terhadap perkembangan social anak usi 5-6 tahun di kampung Cipertani.